Implementasi Model Vark Dalam Penguasaan Kelas Untuk Meningkatkan Prestasi Siswa - Najrul Jimatul Rizki; Siti Qomariyah; Ujang Natadireja; Rubi Babullah; Rima Erviana (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Implementation of the VARK Model (Visual, Auditory, Reading/Writing, Kinesthetic) in the context of classroom mastery is a strategy that can provide a more inclusive and effective approach in increasing student achievement. This research aims to explore how implementing the VARK model can improve students' learning experiences and their academic performance. The research method used is a literature study which involves analysis of relevant sources regarding the VARK concept and its application in an educational context. The research results show that by understanding diverse learning preferences, educators can design learning experiences that better suit students' individual needs. Through the integration of different learning strategies, such as the use of pictures and diagrams for visual students, group discussions for auditory students, reading and writing assignments for students who prefer learning through text, as well as practical activities or experiments for kinesthetic students, students can be more engaged in learning and gaining a deeper understanding. This research also highlights the importance of flexibility in teaching, adapting to changing student learning preferences, and evaluating the effectiveness of the learning strategies used. Although the VARK model has advantages in providing guidance for inclusive teaching, it is important to remember that students' learning preferences can change and that various factors also influence students' academic performance.